A Lanosteryl triterpene from Protorhus longifolia augments insulin signaling in type 1 diabetic rats - Sihle Ephraim Mabhida; Rabia Johnson; Musawenkosi Ndlovu; Nonhlakanipho Felicia Sangweni; Johan Louw; Andrew Opoku; Rebamang Anthony Mosa (BMC, 2018)
Abstract Background A substantial literature supports antidiabetic properties of the lanosteryl triterpene (methyl-3β-hydroxylanosta-9,24-dien-21-oate, RA-3) isolated from Protorhus longifolia stem bark. However, the molecular mechanism(s) associated with the antihyperglycemic properties of the triterpene remained to be explored. The current study aimed at investigating the molecular mechanism(s) through which RA-3 improves insulin signaling in streptozotocin-induced type 1 diabetic rats. Methods The type 1 diabetic rats were treated daily with a single oral dose of RA-3 (100 mg/kg) for 28 days. The rats were then sacrificed, and blood, skeletal muscle and pancreases were collected for biochemical, protein expression and histological analysis, respectively. Results Persistently high blood glucose levels in the diabetic control rats significantly increased expression of IRS-1Ser307 while the expression of p-Akt Ser473, p-GSK-3β Ser9, GLUT 4 and GLUT 2 were decreased. However, enhanced muscle insulin sensitivity, which was indicated by a decrease in the expression of IRS-1ser307 with a concomitant increase in the p-AktSer473, p-GSK-3β Ser9, GLUT 4 and GLUT 2 expression were observed in the diabetic rats treated with RA-3. The triterpene-treated animals also showed an improved pancreatic β-cells morphology, along with increased C-peptide levels. An increase in the levels of serum antioxidants such as catalase, superoxide dismutase, and reduced glutathione was noted in the rats treated with the triterpene, while their serum levels of interleukin-6 and malondialdehyde were reduced. Conclusions It is apparent that RA-3 is able to improve the insulin signaling in type 1 diabetic rats. Its beta (β)-cells protecting mechanism could be attributed to its ability to alleviate inflammation and oxidative stress in the cells.